2009
DOI: 10.1111/j.1540-6210.2009.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Budget Transparency, Fiscal Performance, and Political Turnout: An International Approach

Abstract: Bernardino Benito is a professor of public sector accounting at the University of Murcia in Spain. He has more than 40 publications in national and international books and journals to his credit. He also has directed research programs related to the public sector, especially to the economy, effi ciency, and effectiveness of the different services in this sector. He is a member of the team that established the basic guidelines for accounting reform in the European Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
128
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(144 citation statements)
references
References 22 publications
5
128
0
11
Order By: Relevance
“…Previous studies also confirmed that strengthening the role of the audit as part of the element of governance can improve a country's transparency (Benito & Bastida, 2009;De Renzio & Masud, 2011). It supports the argument that enforcing the level of accountability and transparency by strengthening the SAI can improve the accounting disclosure in a country.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…Previous studies also confirmed that strengthening the role of the audit as part of the element of governance can improve a country's transparency (Benito & Bastida, 2009;De Renzio & Masud, 2011). It supports the argument that enforcing the level of accountability and transparency by strengthening the SAI can improve the accounting disclosure in a country.…”
mentioning
confidence: 48%
“…Studies conducted by Benito andBastida (2009) andDe Renzio andMasud (2011) show that good governance is associated with the level of transparency in a Coefficient test Prob.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign reserves in democracies were higher before elections (Jäger 2016). Transparency may mitigate political budget cycles (Benito and Bastida 2009). On public investment and re-election prospects, see Katsimi and Sarantides (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proposed the usefulness of comparing sustainability transparency practices across different contexts given that the administrative cultures of different countries influence the level of government openness toward citizens and their accountability practices [21].…”
Section: Introductionmentioning
confidence: 99%